David Malouf’s Remembering Babylon as a Reconsideration of Pastoral Idealisation (Journal of the Association for the Study of Australian Literature, 2014)
David Malouf's oeuvre is characterised by a specific treatment of the natural world. Malouf’s sensitivity towards nature is very present in 'Remembering Babylon', inspired by the true story of Gemmy Morrill, ‘lost’ in the ‘wilds’, the novel framed by epigraphs drawn from Romantic poetry. This paper seeks to re-examine this treatment through an ecocritical lens. That is, I seek to explore the novel in terms of its redress of denigrating, exploitative, or idealistic views of human relationships with the non-human natural realm. 'Remembering Babylon' pits characters’ interactions with the natural world in diverse ways and the culminating impression is far from idealistic or apolitical. Ultimately, the novel’s complex rendering of human relationships with place and the non-human animal offers a specific challenge to romanticised visions of place. This argument is counter to some criticism of the novel as idealisation of the natural world at the expense of historically salient political considerations.'Remembering Babylon' explores the significant political issue of human attitudes to the natural realm in complex ways. In order to reconsider the criticism of idealism, the novel is examined in terms of the genre most closely associated with idealisation of the environment: the pastoral. 'Remembering Babylon' appears to have a complex relationship with what can loosely be termed ‘the pastoral’. The novel revises idealising visions of nature and gently parodies the notion that nature is separate from or a tool of human, cultural concerns, particularly through its figurative and literal foregrounding of the nonhuman animal. The epigraph provides a deliberate and significant signal of Malouf’s challenge to pastoral understandings of nature because the poets cited within it, William Blake and John Clare, arguably offer in their wider body of work what might be termed a post-pastoral ethos that evokes, challenges and thus adapts pastoral idealism of nature. The paper suggests that 'Remembering Babylon' expresses such a post-pastoral ethos, if in a very different context and form from Blake and Clare.